The Radicalization of Islam: Case Study of Media Reportage of Boko Haram Insurgency in Northern Nigeria - A. Osho, Sulaiman (Indonesian Journal of Islamization Studies, 2025)
One of the challenges of the world today is the plethora of wars, hostilities, violence, and pogrom engineered by the militarization of religions. From the north, to the south, east and west of the globe, there is religious war cloaked in political gimmicks. And the human devastation continues endlessly in Syria, Iraq, Yemen, Turkey, Iraq, Greater Sahel and Lake Chad Basin, North Eastern Nigeria, South Sudan, Democratic Republic of Congo, Afghanistan, Myanmar, Israel and Palestine, Ukraine, Mexico, and among others including pockets of terrorist acts in United Kingdom and United States. This study examines the radicalization of Islam and its multiplying effects on the peace in the world. It looks at the media reportage of the Boko Haram terrorist religious group in Nigeria. It analyzes the coverage of the insurgencies in the Radio Nigeria news bulletins at the height of the mutinies. It concludes that the coverage of Radio Nigeria of the Boko Haram radicalization in the killing, kidnapping, and destruction of property in the north eastern Nigeria hasn’t reduced the hostilities of the terrorist group. The research offers recommendations for the ways out of the crises.